OPTIMIZATION STRATEGY OF PRODUCTIVE ZAKAT FUNDS AS AN EFFORT TO IMPROVE MUSTAHIK WELFARE (CASE STUDY OF BAZNAS OF PAPUA PROVINCE) - Asnah Abdul Aziz (International Journal Labs, 2024)
The COVID-19 pandemic has an impact on increasing the number of poor people, including in Papua Province. It takes the involvement of all parties in dealing with this impact, one of the parties most considered capable is BAZNAS Papua Province, as a philanthropic institution that functions to manage zakat funds, and one of the objectives of zakat funds is to realize community welfare and poverty reduction. The type of research used in this writing is qualitative research, which is located at BAZNAS Papua Province, with the research subjects coming from the management of BAZNAS Papua Province, namely the Chairman, Deputy Chairman I of the Collection and Distribution Division and the Distribution and Empowerment Section as well as three representatives of productive zakat mustahik. The mechanism for distributing productive zakat funds begins with submitting an application, reviewing the results of the application, survey, until the disbursement of funds then monitoring evaluation and mentoring of fostered partners. Optimizing productive zakat funds requires several strategies including strengthening legality, strengthening effective ZIS collection, transparent management of zakat funds, partnership and collaboration approaches, developing productive programs, technological innovation, strengthening Baznas as amil. A more in-depth study is needed to determine productive mustahiks, maximize business feasibility surveys, and need to add and strengthen assistants who will provide assistance to mustahiks in running their businesses.